2014
DOI: 10.1111/afe.12089
|View full text |Cite
|
Sign up to set email alerts
|

Area-wide monitoring of potato tuberworm (Phthorimaea operculella) by pheromone trapping in Northern Italy: phenology, spatial distribution and relationships between catches and tuber damage

Abstract: 1 The potato tuberworm (PTW) Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae) is key pest of potato in tropical and subtropical regions. From 2002 onward, PTW has emerged as a problem in the Bologna province, the main potato production area in Northern Italy. 2 Field investigations were performed to study the temporal and spatial dynamics of PTW. Adult moths were monitored using pheromone-baited traps over 3 years (2009)(2010)(2011). Traps were georeferenced and catches were analyzed by geostatistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Authors showed that there was a high risk at early pest population stages (mid-June). Geostatistical maps of the spatial distribution of male catches proved to be suitable to analyze the efficacy of Spodoptera littoralis (Boisduval) (Lepidoptera Noctuidae) mating disruption [16] and to study the spatial distribution of vegetable pests including Phthorimaea operculella (Zeller) (Lepidoptera Gelechiidae) and the western corn rootworm Diabrotica virgifera virgifera LeConte, in Northern Italy [29,30]. Moreover, georeferencing tools can be used to decide on the best installation site according to topography and wind direction, when pheromone aerosol devices for mating disruption are intended to be employed [20].…”
Section: Discussionmentioning
confidence: 99%
“…Authors showed that there was a high risk at early pest population stages (mid-June). Geostatistical maps of the spatial distribution of male catches proved to be suitable to analyze the efficacy of Spodoptera littoralis (Boisduval) (Lepidoptera Noctuidae) mating disruption [16] and to study the spatial distribution of vegetable pests including Phthorimaea operculella (Zeller) (Lepidoptera Gelechiidae) and the western corn rootworm Diabrotica virgifera virgifera LeConte, in Northern Italy [29,30]. Moreover, georeferencing tools can be used to decide on the best installation site according to topography and wind direction, when pheromone aerosol devices for mating disruption are intended to be employed [20].…”
Section: Discussionmentioning
confidence: 99%
“…In the mid-1970s, P. operculella was introduced to Iraq [24,55], and by the early 1980s, it was found in Russia [56]. From 2002, P. operculella has emerged as a problem in the Bologna providence in northern Italy [57]. To our knowledge, there are few studies describing the population structure of P. operculella around the world that could explain P. operculella distribution.…”
Section: Moths -Pests Of Potato Maize and Sugar Beetmentioning
confidence: 99%
“…Some studies suggest that the pupal period is not fixed but depends on the temperature at which the larvae grew [104]. [57]. This information suggests a correlation between geographical location, presence or absence of food source, and P. operculella generations per year [14].…”
Section: Pupaementioning
confidence: 99%